Wealth as a Determinant of Comparative Advantage - Wynne, José (American Economic Review, 2005)
This paper shows that a country’s wealth can be an important determinant of comparative advantage when access to credit differs across sectors of the economy. Wealthier nations exhibit a comparative advantage toward goods produced in sectors facing more severe financial imperfections. These sectors are typically populated by small firms. Empirically this paper documents that these sectors are also labor intensive. Consequently, this theory partially offsets traditional sources of comparative advantage and offers an explanation for Trefler’s missing trade mystery and the Leontief paradox. Furthermore, the theory makes the relation between trade and income distribution endogenous.